2017
DOI: 10.1016/j.jalz.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of cancer and Alzheimer's disease risk in a national cohort of veterans

Abstract: INTRODUCTION To examine the risk of AD among cancer survivors in a national database. METHODS Retrospective cohort of 3,499,378 mostly male US veterans ≥65 followed 1996–2011. We used Cox models to estimate risk of AD and alternative outcomes (non-AD dementia, osteoarthritis, stroke and macular degeneration) in veterans with and without a history of cancer. RESULTS Survivors of a wide variety of cancers had modestly lower AD risk, but increased risk of the alternative outcomes. Survivors of screened cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 31 publications
4
97
0
1
Order By: Relevance
“…Interestingly, multiple studies suggest an inverse association between cancer and dementia, in particular for Alzheimer disease (AD) . In 1990, Yamada et al investigated risk factors for dementia in atomic‐bomb survivors and observed that the odds of having cancer prior to AD was 70% lower in patients with AD compared to persons without AD.…”
Section: The Risk Of Cancer In Dementia Patients and The Risk Of Demementioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, multiple studies suggest an inverse association between cancer and dementia, in particular for Alzheimer disease (AD) . In 1990, Yamada et al investigated risk factors for dementia in atomic‐bomb survivors and observed that the odds of having cancer prior to AD was 70% lower in patients with AD compared to persons without AD.…”
Section: The Risk Of Cancer In Dementia Patients and The Risk Of Demementioning
confidence: 99%
“…Few studies investigated the relation of cancer with other diseases including stroke, automobile injuries, osteoarthritis and macular degeneration, which were used as negative control diseases . In case of survival bias, cancer patients would also have a decreased risk of these diseases.…”
Section: The Risk Of Cancer In Dementia Patients and The Risk Of Demementioning
confidence: 99%
See 2 more Smart Citations
“…While diabetes is a known modifiable risk factor for both dementia and cancer, the association between cancer and dementia remains uncertain. Population‐based cohort studies have reported inconsistent risk levels for dementia among individuals with cancer . We therefore conducted a cross‐sectional survey using a prospective Japanese cohort to examine whether having cancer or comorbid cancer and diabetes from midlife increases the risk of physician‐diagnosed dementia.…”
Section: Risks Of MCI Dementia and Cd After Incidence Of Cancer Or mentioning
confidence: 99%